2020
DOI: 10.1016/j.cll.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Panels and Syndromic Testing in Clinical Microbiology

Abstract: Syndromic panels have allowed clinical microbiology laboratories to rapidly identify bacteria, viruses, fungi, and parasites and are now fully integrated into the standard testing practices of many clinical laboratories. To maximize the benefit of syndromic testing, laboratories must implement strict measures to ensure that syndromic panels are being used responsibly. This article discusses commercially available syndromic panels, the benefits and limitations of testing, and how diagnostic and laboratory stewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…And the result of our study also showed that patients infected with multiple pathogens spend about 1 day longer and an extra RMB 1000 than patients infected with a single pathogen. However, the results are mixed about the clinical symptoms and health economic burden for patients with pertussis with or without coinfections ( 27 ). Some studies showed that pertussis-RSV coinfections tended to be more severe ( 26 ) and were associated with higher rates of wheezing and readmission and a more extended hospital stay ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…And the result of our study also showed that patients infected with multiple pathogens spend about 1 day longer and an extra RMB 1000 than patients infected with a single pathogen. However, the results are mixed about the clinical symptoms and health economic burden for patients with pertussis with or without coinfections ( 27 ). Some studies showed that pertussis-RSV coinfections tended to be more severe ( 26 ) and were associated with higher rates of wheezing and readmission and a more extended hospital stay ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular tests for single pathogens and multi-pathogen panels can also help identify possible etiologic agents in samples taken from febrile children. 13 Early identification of pathogens for which antimicrobial is not necessary (such as enterovirus and human herpesvirus 6) could allow treating clinicians to safely avoid antibiotic initiation or to discontinue unnecessary antimicrobial therapy early. 13 As for inflammatory marker testing, pathogen-specific testing is more useful to avoid antimicrobial use rather than to prompt the initiation of antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons why laboratories may be reluctant to use molecular tests to detect CPOs and differentiate among CRG classes in resistant bacterial isolates. The cost of the tests is often cited as an issue, especially for the genotypic assays ( Burnham et al., 2017 ; Pereckaite et al., 2018 ) but the reluctance to use molecular tests clearly goes beyond this issue as syndromic test panels are broadly used in clinical microbiology laboratories despite their increased costs over traditional identification methods ( Dien Bard and McElvania, 2020 ). For many laboratories in the United States, there is a sense that differentiation among CRG is simply unnecessary, as it is presumed that CPOs are likely to be KPC-producers ( Miller et al., 2017 ).…”
Section: Reluctance To Using Molecular Diagnostic Tests For Cpo Detectionmentioning
confidence: 99%
“…Unfortunately, the data supporting the value of including CRG in syndromic panels (several of which are listed in Table 2 ) to improve anti-infective therapy currently remain sparse ( Dien Bard and McElvania, 2020 ). In many reports, the low prevalence of CPO containing a CRG of interest has hindered the accumulation of outcome data.…”
Section: Molecular Tests To Identify Resistance Genes In Positive Blood Culture Bottles and Respiratory Specimensmentioning
confidence: 99%